Association of Blood Cadmium Level with Cardiometabolic Risk Factors and Liver Enzymes in a Nationally Representative Sample of Adolescents: The CASPIAN-III Study - Kelishadi, Roya (Hindawi Publishing Corporation, 2013)
Introduction. This study aimed to determine the association of blood cadmium level with cardiometabolic risk factors and liver enzymes in adolescents. Methods. This case control study comprised 320 Iranian adolescents, 160 with metabolic syndrome and an equal number of controls. They were selected from participants of a nationwide survey entitled the CASPIAN-III study. Cadmium was measured by atomic absorption method. Results. The mean age of the case and control groups was not significantly different (15.3 ± 2.6 versus 14.63 ± 2.5 years, resp., P > 0.05). The mean cadmium level was near double-fold higher than the standards of the World Health Organization, without significant difference between the MetS and control groups (10.09 ± 2.21, 9.97 ± 2.38 μg/L, resp., P > 0.05). Cadmium level had positive but nonsignificant correlations with diastolic blood pressure, serum triglycerides, fasting blood glucose, LDL-C, and liver enzymes. Conclusion. Cadmium level had positive but nonsignificant association with some cardiometabolic risk factors and liver enzymes. The associations did not reach statistical significant level, and this may be because of the high levels of cadmium in both groups studied or because of the young age group of participants. Controlling environmental pollutants shall be a priority for the prevention of chronic diseases.